Հայաստանի գյուղատնտեսությունը մ. թ. ա. VI–IV դդ. - Գայանե Քոչարյան (ՀՀ ԳԱԱ հրատ.)
Сравнительный анализ данных археологии, палеоботаники, палеофауны и письменных источников дает представление о процессе развития сельского хозяйства Армении VI–IV вв. до н. э. – восстановление основных каналов ирригационной сети предшествующих времен, применение ранее освоенных специальных агротехнических мероприятий, возделывание зерновых, садовых, огородных, технических культур, развитие традиционных отраслей – виноделия, пивоварения, маслоделия, а также скотоводства, птицеводства и коневодства – снабжающих продуктами питания и ремесленного сырья. Традиционно продолжается натурально-хозяйственный уклад жизни сельских общин, объединенных вокруг административно-хозяйственного центра. The comparative analysis of archeological, palaeobotanical, palaeozoological and written sources data sheds light on the process of development of agriculture in the given period of Armenia. All the facts point to the recovery of the basic channels of irrigational network of previous times, the application of special agrotechnical measures, the cultivation of grain, horticultural, technical crops and vegetables, the development of traditional branches of viniculture, brewing, oil producing as well as cattle-breeding, poultry breeding and horse breeding–supplying with foodstuff and craft raw materials. The natural-economic way of life of rural communities united round the administrative centre is being traditionally proceeded.
Keywords: History; Agriculture; D History